Alternatives for the control of powdery mildew (Oidium sp.) in cucumbers (Cucumis sativus L.) - Yáñez Juárez Moisés Gilberto; León de la Rocha Jorge Francisco; Godoy Angulo Tirzo Paúl; Gastélum Luque Roberto; López Meza Miguel; Cruz Ortega, Jacobo Enrique; Cervantes Díaz Lourdes (Revista Mexicana de Ciencias Agrícolas, 2018)
This research was conducted to know the effect of phosphorous and potassium salts in the growth and control of powdery mildew (Oidium sp.) in cucumbers. Cucumber plants of the variety Poinset 76 with signs of the disease were sprayed with potassium bicarbonate, sodium bicarbonate, monopotassium sulphate, potassium nitrate, potassium chloride and potassium phosphite solutions. The application of salts showed no significant effects (p≤ 0.05) on the height and number of leaves of plants evaluated. With potassium phosphite, the incidence of the disease varied between 27.9 and 32.4%; with potassium bicarbonate, it was between 19.9 and 29.5%, and in the control, variation went between 44.1 and 47.4%. Twenty-six days after the first application (dda), plants treated with potassium bicarbonate and potassium phosphite showed 67.7 and 62.0% less severity than the controls. Forty-two dda with potassium bicarbonate and potassium phosphite, there was 49.4 and 44.5% less severity than in the control. Results showed that the potassium phosphite and potassium bicarbonate at 5 and 4.7 g L, respectively, reduced signif icantly (p≤ 0.05) the incidence and severity of the disease.